Influence of Evaluation System on Effectiveness of Foreign Students' Mathematical Education; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Sherstneva A. I. Anna Igorevna; Imas O. N. Olga Nikolaevna; Galanova N. Yu. Nataliya; Tran Van Tuan (2015, 2015)
Title screen